Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I am asked to minimize $\sum^n_{i=0}(x_i - C)^2$ with respect only to C so I know I have to take the derivative respect to C, set it equal to 0, and then solve. I have never done summation in my life and this is very new. I have been trying to search the web for information about how to proceed in this cases but all I have found is long theorems of summation or explanayions of very simple operations with summation notation. I have found nevertheless the answer to my question whis is as follows: $$S = \sum^n_{i=0}(x_i - C)^2$$

$$\frac{\partial S}{\partial C} = \sum^n_{i=0} 2 (x_i - C)(-1) = -2 \sum^n_{i=0} (x_i - C)$$

$$\frac{\partial S}{\partial C} = 0 \implies \sum^n_{i=0} (x_i - C) = 0$$

$$ \sum^n_{i=0} x_i - \sum^n_{i=0} C = 0$$

$$ \sum^n_{i=0} x_i = \sum^n_{i=0} C = nC$$

$$C = \frac{\sum^n_{i=0} X_i}{n}$$

First step , I don't get what this guy is doing, so when he takes the derivative why he puts that (-1) at the end? is it because is originally the square of a difference? that's the only thing I can think of..

Second step, where has the -2 gone? just vanished.

Third step, I get this one.

Fourth, what the hell? what is this nC comng from? what does it mean? I understand that at the end what he is doing is $ \sum^n_{i=0} x_i= nC$ so isoltaes C and he finnally gets the result $C = \frac{\sum^n_{i=0} X_i}{n}$. Any reasons though why he chooses to swap $\sum^n_{i=0} C$ instead of $\sum^n_{i=0} x_i$ for $nC$?

Thanks a lot, I'd really appreciate if you could please refer me to any page you might know about summation which doesnt go about 1000 theorems and properties . Unfortunately I can spend much time on sumation as I have many other topics in my exam I need to cover and that's just a a very little part of it. Cheers

share|improve this question

3 Answers 3

up vote 1 down vote accepted

First step

Think of the sum as a function. To find a minima/maxima for a certain function we need to find it's derivative and set it to 0. And because we have 2 terms in between the parenthesis, we can't just apply the rule $\frac{\partial}{\partial x} x^n = nx^{n-1}$, but instead we apply the chain rule. So that -2 is from the chain rule.

Second step

Let's denote the derivative of the sum as $S_1$, the when $2S_1 = 0$? It's only possible if $S_1 =0$, so we left out the 2.

Fourth step

$C$ is a constant that's independent from $n$ so after every step we just add $C$. If $n$ is the number of steps then we have added $nC$

share|improve this answer

Consider $f(C)=\sum_{i=1}^{n}(x_{i}-C)^{2}$ so by chain rule the derivative of $f$ is:

$f'(C)=\sum_{i=1}^{n}2(x_{i}-C)(-1)$.

To minimize at a differentiable point we need that $f'(C)=0$ so the above is $0$ when:

$0=-\sum_{i=1}^{n}(2x_{i}-2C)$

Multiplying both sides by $-1$ we get

$0=\sum_{i=1}^{n}(2x_{i}-2C)=2\sum_{i=1}^{n}x_{i}-2\sum_{i=1}^{n}C=2\sum_{i=1}^{n}x_{i}-2C\sum_{i=1}^{n}1=2\sum_{i=1}^{n}x_{i}-2Cn$.

$\sum_{i=1}^{n}1=n$ since $\sum_{i=1}^{n}a_{i}=a_{1}+...+a_{n}$ by definition and we can take $a_{i}=1$ for all $i$.

So

$2Cn=2\sum_{i=1}^{n}x_{i}$

Dividing by $2n$ we get $C=\frac{\sum_{i=1}^{n}x_{i}}{n}$

share|improve this answer
    
Thanks very much for your answer. When you have 2Σ Xi - 2ΣC and you go 2Σ Xi - 2C Σ 1 , why dont you do the same with the 2Σ Xi? So it becomes 2 x1 Σ 1? Sorry though, about not writing it in proper notation. Cheers –  Maximilian1988 Sep 14 '13 at 2:25
1  
You can't pull the $x_{i}$ out of the sum since it depends on the index $i$. –  user71352 Sep 14 '13 at 2:29
    
Ok, thanks a lot for your answers. You have been indeed very helpful. :) –  Maximilian1988 Sep 14 '13 at 2:30
1  
Your welcome. Always happy to help. –  user71352 Sep 14 '13 at 2:31

Step 1: the $-1$ comes from the chain rule.

Step 2: We set the derivative equal to $0$, then divide both sides by $2$. That's why the $2$ goes away.

Step 4: $C + \cdots + C = nC$. ($C$ appears $n$ times on the left.)

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.